Crystallization of a 45 kDa peroxygenase/peroxidase from the mushroom Agrocybe aegerita and structure determination by SAD utilizing only the haem iron - Piontek, Klaus (International Union of Crystallography, 2010)
Some litter-decaying fungi secrete haem-thiolate peroxygenases that oxidize numerous organic compounds and therefore have a high potential for applications such as the detoxification of recalcitrant organic waste and chemical synthesis. Like P450 enzymes, they transfer oxygen functionalities to aromatic and aliphatic substrates. However, in contrast to this class of enzymes, they only require H(2)O(2) for activity. Furthermore, they exhibit halogenation activity, as in the well characterized fungal chloroperoxidase, and display ether-cleavage activity. The major form of a highly glycosylated peroxygenase was produced from Agrocybe aegerita culture media, purified to apparent SDS homogeneity and crystallized under three different pH conditions. One crystal form containing two molecules per asymmetric unit was solved at 2.2 Å resolution by SAD using the anomalous signal of the haem iron. Subsequently, two other crystal forms with four molecules per asymmetric unit were determined at 2.3 and 2.6 Å resolution by molecular replacement.